Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques